The theory of island biogeography and soundscapes: Species diversity and the organization of acoustic communities. (7th June 2019) - Robert, Aloïs; Lengagne, Thierry; Melo, Martim; Gardette, Vanessa; Julien, Sacha; Covas, Rita; Gomez, Doris; Doutrelant, Claire
Abstract: Aim: On islands, species richness is reduced and interspecific competition relaxed in relation to the mainland, allowing species to use broader ecological niches. These factors are known to affect diet and morphology, but can also affect communication and acoustic signalling in particular. However, no study has ever compared insular and continental soundscapes to determine to which extent islands present reduced acoustic richness (number of co‐vocalizing species) and fewer constraints for vocalizing species. Location: São Tomé Island, Mount Cameroon, Madeira Island, Southern France. Taxon: Birds. Methods: We compared two pairs of insular and continental soundscapes: one in a temperate zone, the other in the tropics. We recorded sounds produced in similar types of primary forests and measured acoustic richness and ambient noise profiles. We then assessed acoustic niche organization by computing, for each community, species turnover, temporal and frequency overlaps, and acoustic avoidance. Results: We found fewer species co‐vocalizing on islands compared to mainland and in temperate compared to tropical region. Ambient noise was louder in the tropics and occupied a wider frequency range, especially on the mainland, thereby revealing a reduction in available acoustic space for tropical mainland birds. In this more crowded and noisy soundscape, species presented a higher acoustic turnover, overlapped less in time and in frequency with each other and acoustically avoided each other more when compared to the three other communities. Main conclusions: Soundscapes differed and imposed fewer constraints on vocalizing species along the species diversity gradient from tropical mainland to temperate island. Acoustic niche partitioning increased with species richness and was associated with increased levels of acoustic interference. Results set a scene for an effect of relaxed competition on song evolution on islands, especially in the tropics.